Collocation Errors In Indonesian Efl Learners’ Composition - Yeni Arif Rahman (Journal of English Language Learning, 2021)
Collocation errors are often made by Indonesian EFL learners in essays. The error, which is part of learning process, stems from inter and intra language. The study aims to identify and quantify the collocation error in students’ composition. The data were 20 argumentative essays collected from students’ final paper work of universitas Bina Sarana Informatika majoring in English study. The study employs collocation identification procedure to identify grammatical and lexical collocation. The result was then compared with the standard collocation to produce standard and non-standard (error) collocations. The result shows that 25 % or 14 out of 55 grammatical collocation contain error while lexical collocations error is dominated by verb + noun lexical collocation which take  10 % of total amount of lexical collocations in use and in total there are 23 errors of 147 collocation in use or 15 % lexical collocation error. From the result, it can be inferred that lexical collocation error appear more frequently than grammatical collocation error.